The Role of Neural Plasticity in Depression: From Hippocampus to Prefrontal Cortex - Wei Liu; Tongtong Ge; Yashu Leng; Zhenxiang Pan; Jie Fan; Wei Yang; Ranji Cui (Neural Plasticity)
Neural plasticity, a fundamental mechanism of neuronal adaptation, is disrupted in depression. The changes in neural plasticity induced by stress and other negative stimuli play a significant role in the onset and development of depression. Antidepressant treatments have also been found to exert their antidepressant effects through regulatory effects on neural plasticity. However, the detailed mechanisms of neural plasticity in depression still remain unclear. Therefore, in this review, we summarize the recent literature to elaborate the possible mechanistic role of neural plasticity in depression. Taken together, these findings may pave the way for future progress in neural plasticity studies.